Environmental Policy and Gender Health Gap - Liwen Guo; Zhiming Cheng; Massimiliano Tani; Sarah Cook (Institute of Labor Economics (IZA), 2023)
Utilizing a nationally representative panel data of middle-aged and elder individuals from China, we assess the health impact of environmental policies, with special attention paid to gender disparities within their effects. This study utilizes thermal inversions to address the endogeneity of air pollution and constructs a fixed effects model. Our findings highlight that the negative impact of air pollution on female health is significant, particularly for females in the middle of the health distribution. Notably, the implementation of environmental policies leads to health improvements in females and plays a key role in bridging the health gap between genders. These findings provide compelling evidence of the importance of environmental policy in promoting health equity.
Keywords: C21; I14; J71; Q53; Q58; 330; environmental policy; gender health gap; China